The Electoral Failure of the Indonesian Solidarity Party in the 2024 Legislative Elections - Putra, Anselmus Herosolimitanus Gafita; Herdiansah, Ari Ganjar; Paskarina, Caroline (RMPI-BRIN, 2025)
Despite adopting a digital platform and receiving support from national political figures, including President Joko Widodo and Kaesang Pangarep, who became the party's chairman, the Indonesian Solidarity Party (PSI) suffered an electoral failure in the 2024 legislative elections. This journal analyzes the factors behind this failure. Adopting the digital party concept perspective, the study reveals that the PSI's electoral failure was due to its failure to implement digital platform logic in its governance. This study employs a qualitative descriptive approach, utilizing a theory-based case study method and data collected through interviews with a PSI division head and PSI cadres, to analyze this phenomenon. Secondary data from scientific literature and digital media also support the study. The findings reveal that the PSI was unable to establish a comprehensive operational system. Furthermore, the PSI's digital transformation was not substantive or holistic. PSI has not established a participatory digital membership system, an open cadre mechanism for selecting leadership candidates, a deliberative channel for developing programs and policy objectives, or a two-way communication system for shaping its public image. PSI's resources are not managed transparently, nor are they used to build a digital ecosystem aligned with the five pillars of a digital party. As a result, PSI has been unable to establish a superbase, an active and loyal community of supporters, to serve as the party's main strength. In the context of open proportional elections, the PSI lacks a mechanism to support its candidates through its digital platform. Thus, the party's digital visibility cannot be converted into electoral votes. Additionally, support from political elites cannot significantly impact the party's electoral results due to the lack of an ideal, systemic institutionalization of the party. PSI relies too heavily on Jokowi and Kaesang. This study shows that digital parties cannot function solely by relying on digital platforms; they also require institutionalization as robust political structures.